2018
DOI: 10.3389/fgene.2018.00464
|View full text |Cite
|
Sign up to set email alerts
|

First Replication of the Involvement of OTUD6B in Intellectual Disability Syndrome With Seizures and Dysmorphic Features

Abstract: Biallelic mutations in the ovarian tumor domain-containing 6B (OTUD6B) gene, coding for a deubiquitinating enzyme, were recently described to cause an intellectual disability syndrome characterized by seizures and dysmorphic features in six families worldwide. We here report on a 6-year-old Italian girl, presenting mild intellectual disability, speech and motor delay, and recurrent seizures, who came to our attention after being screened for genes responsible for Rubinstein–Taybi syndrome, Kabuki syndrome, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(30 citation statements)
references
References 15 publications
2
28
0
Order By: Relevance
“…Recent studies found that biallelic pathogenic variants in OTUD6B in 12 individuals from 6 independent families with an intellectual disability syndrome associated with seizures and dysmorphic features. [ 50,51 ] Homozygous OTUD6B knockout mice were dead at the birth day, smaller in size, and had congenital heart defects. [ 50 ] Here, we found that OTUD6B knockdown dramatically enhances migration features of human HCC cells in vitro and in vivo.…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies found that biallelic pathogenic variants in OTUD6B in 12 individuals from 6 independent families with an intellectual disability syndrome associated with seizures and dysmorphic features. [ 50,51 ] Homozygous OTUD6B knockout mice were dead at the birth day, smaller in size, and had congenital heart defects. [ 50 ] Here, we found that OTUD6B knockdown dramatically enhances migration features of human HCC cells in vitro and in vivo.…”
Section: Resultsmentioning
confidence: 99%
“…Our patient’s clinical features were initially compatible with the diagnosis of Kabuki syndrome (OMIM 147920) and consistent with other reports. 2 , 3 Other diagnoses, such as Rubinstein-Taybi syndrome (OMIM 180849) and DiGeorge syndrome (OMIM 188400), among others, had been suggested as differential diagnoses. Consequently, diagnosing cases with partially overlapping complex phenotypes warrants the use of broad genetic tests, such as exome sequencing.…”
Section: Discussionmentioning
confidence: 99%
“…Later, 3 other cases were detected after a genetic research odyssey was undertaken, also by ES. 2 - 4 …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations